DAMPAK EKONOMI DAN SOSIAL ALIH FUNGSI LAHAN PERTANIAN HORTIKULTURA MENJADI KAWASAN WISATA BUKIT RURUKAN DI KECAMATAN TOMOHON TIMUR, KOTA TOMOHON - Elisabeth ., Ante; Noortje M. Benu; Vicky R.B Moniaga (Sam Ratulangi University, 2016)
This research aims is to describe the impact of Horticulture land conversion to farmer’s economy condition and socio-cultural condition that has sold their land to be made into tourist attraction. Research carried out in May until July 2016. Data used is primary data that obtained from interview to 6 (six) respondents and secondary data obtained from Rurukan Office village. Research result shows that the cause of land conversion is high offer price and the sale of land used for opening business in the tourist attraction . the positive impact of land conversion one of them is employment, because the majority of workers and businessman in the tourist attraction is from Rurukan village. Research result also identifying negative impact to locals because of the noises from tourist attraction and the disappearing of local’s cultures.